Discursive Analysis of the Written Compositions of STEM Grade-11A Students: A Grounded Theory - Purcia, E L (KnE Social Sciences, 2018)
The written corpora by the STEM Grade-11A students of Calbayog City National High School for the school year 2017-2018 were identified, categorized and analyzed to know the common discursive errors they committed. Initially bounded from Ferris (2005) error analysis model, the researcher analyzed the most recurrent errors that students committed in succeeding writing activities that lasted until the end of the first semester. The result of which was the basis for the theory evolved. The findings showed that the students commonly committed lexical, mechanical, syntactical and morphological errors since most of their errors revealed exceptionally high values in these categories thus; the researcher concluded that students would likely fail to construct written discourses correctly because of these failures. A theory on analyzing errors among written discourses was evolved in order to help students improve their writing skills and combat chances of committing errors. Keywords: Discursive Analysis, Corpora, Theory Evolved